Analysis Role in the Strategy of Post-Crisis Management - M., Baydildina A. (Farabi Journal of Social Sciences, 2019)
Abstract. Article regards the problem of analyzing the consequences of the financial crisis in terms of impact on the value of the business in order to apply the procedures of restructuring, taking into account the current legal framework. The solution to this problem is to solve the scientific problem of adapting existing mathematical and instrumental methods of business valuation in the Republic of Kazakhstan. The implementation of these objectives envisages the solution of problems of business management in the conditions of the crisis through the application of various strategies of company management.